Combatting medical corruption: A global review of root causes, consequences, and evidence-based interventions - Qudah, Anas M Al; Al-haddad, Lara; Aljabali, Alaa A A (International Journal of Innovative Research and Scientific Studies, 2025)
Medical corruption poses a widespread and growing threat to healthcare systems globally, with the World Health Organization estimating that 10-25% of global healthcare spending is lost annually to corrupt practices. This systematic review synthesizes existing evidence on the causes, socioeconomic and clinical impacts, and effectiveness of anti-corruption interventions. We critically examine manifestations of corruption, such as bribery, fraudulent billing, kickbacks from pharmaceutical companies, and systemic inequities driven by unethical practices, including informal payments for care. A literature review was conducted across the PubMed, Scopus, and Web of Science databases (2013–2024), screening 1,250 peer-reviewed articles and case studies, with 89 selected. These findings indicate that corruption disproportionately impacts vulnerable groups, leading to medication shortages, unequal access to care, and preventable deaths. Low- and middle-income countries lose 30% of their healthcare funds to corruption, compared to 5-10% in high-income nations. Ongoing barriers to reform include regulatory capture, cultural normalization of bribery, and the lack of whistleblower protections. Emerging technological solutions, such as blockchain for supply chain transparency, AI-driven fraud detection, and crowdsourced corruption-reporting platforms, promise to combat illegal activities. However, anti-corruption interventions must be context-specific, incorporating robust legal frameworks, culturally sensitive ethics training, and international cooperation to address cross-border pharmaceutical fraud. This review uniquely advocates for institutional accountability metrics and the integration of anti-corruption goals into universal health coverage agendas. Policy implications underscore the necessity of political will to dismantle entrenched networks and public-private partnerships to ensure equitable care. Future research should focus on longitudinal studies to assess intervention effectiveness and explore the role of social determinants in exacerbating corruption.